Effect of urea level in protein supplements on performance by beef cows consuming low-quality, tallgrass-prairie forage - Woods, B.C.; Cochran, R.C.; Mathis, C.P.; Heldt, J.S.; Olson, K. C.; Titgemeyer, Evan C.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred thirty two Hereford × Angus cows grazing tallgrass-prairie range during winter were used to evaluate the effects of varying the amount of supplemental degradable intake protein (DIP) derived from urea on cow and calf performance. Treatment groups were: 0, 15, 30, and 45% of the supplemental DIP from urea. Supplements were formulated to contain 30% crude protein (CP), with approximately 70% of the CP being DIP. Palatability was not a significant problem within the range of urea inclusion tested. In general, prepartum weight and condition losses were greater with increasing levels of urea, although the magnitude of condition loss was greater when urea comprised more than 30% of the DIP. Calf performance was not affected by treatment.
Keywords: Beef; Cows; Forage; Urea; Performance